(untitled) (Research, Society and Development, 2025)
These professionals’ perceptions of the death and dying process reveal different emotional, rational, and social dimensions that, combined, directly influence quality of life and professional performance. This research aims to investigate the psychological impacts faced by emergency nurses when coping with death. This is a bibliographic and field study with a qualitative and quantitative approach, based on the analysis of scientific articles available in electronic databases to provide theoretical support for interviews with 10 nurses working in an emergency hospital. The results confirm that constant exposure to death, combined with work overload and the lack of adequate psychological support, favors the development of emotional and mental disorders, compromising both individual health and patient care. The conclusion is that the issue in question is complex, multifactorial, and requires special attention from healthcare institutions. It is essential to promote discussions and implement public policies and management strategies that prioritize the psychological care of emergency nurses, recognizing the importance of institutional support and professional development. Therefore, this study seeks to raise awareness of the importance of these workers’ mental health and encourage the creation of prevention, support, and emotional strengthening measures in the workplace.